Dakwah Dalam Paradigma Pemberdayaan Masyarakat Muslim - Aziz, Rohmanur (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2010)
The concept of dakwah within the contemporary context of study puts emphasis on developmental dakwah focusing on community empowerment. This concept bears relevance to core problems suffered by Muslim peoples, especially including poverty, ignorance, being suppressed, backwardness, inability, and other weaknesses. The empowerment concept of dakwah could not rely only on istinbÃ¢th procedure, but it could also be further developed by ways of adaptation from other social sciences through iqtibÃ¢s and istiqrÃ¢â scientific procedures.